A study of ichthyoparasites from imported ornamental fish from Indonesia and Sri Lanka and possible host-parasite interactions and - Lukhele, Linda Prince (My University, 2024)
The current study aimed to investigate the prevalence, mean intensity and parasite composition from fishes imported from Sri Lanka to determine the effectiveness of Sri Lanka’s treatment strategy against parasite infestations, and to determine the host-parasite interactions between Glossolepis incisus from Indonesia and its associated parasites. The keeping of ornamental fish has become a popular hobby among millions of enthusiasts worldwide, including in South Africa. Most ornamental fish sold on the South African market are alien and imported from countries such as Sri Lanka and Indonesia. Ornamental fish along with their parasites can be introduced into local aquatic systems. The repercussions of introducing alien ichthyoparasites to native species have been documented. However, currently, in South Africa, the legislation does not require that imported fish destined for the pet industry be quarantined or treated against parasites. Sri Lanka has gained a reputation for effectively treating ornamental fish before exporting them to other countries. In this study, 11 ornamental fish species from nine families were imported via WCB Import from Sri Lanka (n = 10) and Indonesia (n = 1) and examined for parasites within 24 hours of their arrival in South Africa. In the laboratory, fish were sacrificed by percussive stunning and cervical transection, dissected, and the organs were placed in Petri dishes and scrutinised for parasites through a compound microscope, whilst skin smears were scrutinised under a stereo microscope. Observed parasites were collected and preserved using standard methods and their prevalence and mean intensity were determined. Of the 10 species received from Sri Lanka and examined, five were found to be infected by parasites. Two groups of parasites were collected from the fishes, these being Branchiura and Monogenea, with monogeneans being the most dominant. Branchiura was represented by a single species, whilst Monogenea was represented by five genera and eight species. A single specimen of branchiuran was collected from C. auratus and identified as Argulus japonicus. Monogeneans collected from C. auratas were Dactylogyrus baueri, Dactylogyrus intermedius, Gyrodactylus gurleyi and Gyrodactylus kobayashii. In turn, Hypostomus plecostomus was infected by the monogenean Heteropriapulus heterotylus with Metynnis hypsauchen, Pangasianodon hypophthalmus and Barbonymus schwanenfeldii each infected by Urocleidoides sinus, Thaparocleidus caecus and Dactylogyrus lampam respectively. Branchiura recorded the lowest prevalence and iv intensity at 6.7% and 1% respectively. The prevalence for monogenean parasites varied between 60% for H. heterotylus from H. plecostomus and 100% for T. caecus from P. hypophthalmus. The mean intensity for monogenean parasites varied between 5.1 for H. heterotylus from H. plecostomus and 224.2 for T. caecus from P. hypophthalmus. In a separate trial, host-parasite interactions using Glossolepis incisus were investigated over nine weeks. Upon arrival at the University of Limpopo, Parasitology Laboratory, 15 specimens were sacrificed and examined for parasites. The next week another 15 specimens were examined. Thereafter, on a biweekly basis, 15 specimens that were housed in aquaria were randomly selected and examined for parasites. The nematode Camallanus cotti and a new monogenean species (Ancryocephalidae n. gen.) were collected from the fish examined. Throughout the trial, no trend in parasite numbers was observed for monogeneans. However, a high ammonia concentration and eutrophication were associated with an increase in monogenean numbers. A decrease in nematode numbers was observed due to these parasites having a lower survival rate under aquarium conditions thought to be due to the absence of the intermediate host. Water changes and reduced fish congestion were also linked to a decrease in both monogenean and nematode numbers. Monogeneans generally share very similar morphological features, and thus their identifications have to be genetically confirmed. Amongst the collected monogenean species in the current study, the 18S, ITS1 and 28S rDNA segments were successfully sequenced for only T. caecus and Ancyrocephalidae n. gen. Two haplotypes of T. caecus were revealed. Therefore, the current study recognises the need to re-evaluate the morphometry of the typematerial of T. caecus, to establish which genotype represents T. caecus and which would be a new species of high morphological similarity to T. caecus. Ancyrocephalidae n. gen. was genetically confirmed to be a new monogenean species. The current study therefore presents the first DNA sequencing of 18S, ITS1 and 28S rDNA segments of monogenean parasites collected from the host species G. incisus. Since some of the fishes examined in this study were observed to be infected with parasites, the risk of their introduction and possibly invasion into local systems still exists. The current study therefore recommends that the South African authorities at customs put in place quarantine and treatment protocols for live fish imported into the country.
Thesis (M.Sc. (Zoology)) -- University of Limpopo, 2024
Keywords: Parasites; Fish parasites; Sri Lanka; Indonesia; Host-parasite interactions; Fishes -- Parasites; Ornamental fish trade